Calibration and validation of AquaCrop for deficit and full irrigation of tomato - Darko, Ransford Opoku; Shouqi, Yuan; Haofang, Yan; Liu, Junping; Abbey, Agnes (International Journal of Agricultural and Biological Engineering, 2016)
The objective of this study was to calibrate and test AquaCrop for tomato (Lycopersicon esculentum) grown under deficit and full irrigation. Two field experiments were carried out in the tropical humid coastal savanna zone in Mfantseman district of the Central Region of Ghana. Data from the first experiment were used to calibrate the model while data obtained from the second experiment were used to validate the model. The calibrated AquaCrop model concentrated on its performance to predict crop yield and seasonal crop water requirement (ETc). Four treatments were investigated: T1 (no irrigation after plant establishment), T2 (50% ETc restoration), T3 (100% ETc restoration up to beginning of flowering, then 50% ETc restoration) and T4 (100% ETc restoration). The results revealed that AquaCrop was able to simulate the yield of tomato for T2-T4 with the exception of Treatment T1 which was simulated with the highest deviation of 45.1%. On the other hand, the model was able to simulate the seasonal water requirements to an appreciable degree in both experiments. It must be pointed out that the calibration of AquaCrop suffered from a lack of data on the progress of crop canopy cover which is a very important parameter used in developing the model. Keywords: AquaCrop, irrigation, calibration, validation, tomato, water requirements, yield DOI: 10.3965/j.ijabe.20160903.1812 Citation: Darko R O, Yuan S Q, Yan H F, Liu J P, Abbey A. Calibration and validation of AquaCrop for deficit and full irrigation of tomato. Int J Agric & Biol Eng, 2016; 9(3): 104－110.